Mechanisms of unimodal and cross-modal interference - Hirst, Rebecca (2019)
Background: In everyday life we must frequently ignore distractions arising from multiple senses. However, most of our understanding about this cognitive process (known as interference control) is derived from unimodal paradigms, in which relevant and irrelevant information are presented in the same sense. Thus, it remains unclear whether the mechanisms proposed to underpin unimodal interference control generalise to cross-modal contexts.